DISKURSUS HISTORIS MUHAMMADIYAH DI KOTA AMBON - Laisouw, Yusup; Loilatu, Abd Muin (IAIN Ambon, 2022)
Muhammadiyah which was founded by KH. Ahmad Dahlan on November 18, 1912 in Kauman Yogyakarta, is one of the modernist and reformist Islamic organizations in Indonesia that has made good history, especially in the city of Ambon. Muhammadiyah Association is one of the amar ma'ruf nahi munkar Islamic movements. Muhammadiyah's historical discourse was officially established in Ambon City in 1932 by holding Hisbul Wathan scouting activities under the leadership of Hisbulwathan (HW) activist Saleh Kastrol Saparwi in Ambon. Since the presence of Muhammadiyah in Ambon City, Muhammadiyah members have sprung up in Ambon City: 'Aisyiyah, Hisbulwathan, Muhammadiyah Youth, Nasyiatul 'Aisyiyah, Muhammadiyah Student Association, Muhammadiyah Student Association, Tapak Suci Putra Muhammadiyah.Keywords: Discourse, history, Muhammadiyah Ambon City